2013
DOI: 10.4025/enfoque.v32i1.16761
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho econômico e a responsabilidade social corporativa: uma contribuição para a análise da relação destas variáveis no caso das maiores companhias abertas Brasileiras

Abstract: Desempenho econômico e a responsabilidade social corporativa: uma contribuição para a análise da relação destas variáveis no caso das maiores companhias abertas Brasileiras investigating the 100 largest publicly traded companies by market capitalization, listed and not listed on the BM&FBovespa ISE. By applying logistic regression results indicate a positive and significant relationship between economic performance and corporate social reputation. This result is consistent with the findings of previous researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
4
0
2
Order By: Relevance
“…From the selected sample of 68 companies, 26 are listed on the ISE (CSI) of BM&FBOVESPA, which considers the aspect of corporate sustainability, based on economic efficiency, environmental balance, social justice and CG. It was taken into account that the companies listed on the ISE use CSR as a strategy to increase the return of their actions (Almeida-Santos et al , 2013) or their financial performance (Bear et al , 2010).…”
Section: Methods and Procedures Of Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…From the selected sample of 68 companies, 26 are listed on the ISE (CSI) of BM&FBOVESPA, which considers the aspect of corporate sustainability, based on economic efficiency, environmental balance, social justice and CG. It was taken into account that the companies listed on the ISE use CSR as a strategy to increase the return of their actions (Almeida-Santos et al , 2013) or their financial performance (Bear et al , 2010).…”
Section: Methods and Procedures Of Researchmentioning
confidence: 99%
“…Empirical research found evidence of a positive correlation between the proportion of women and corporate performance (Erhardt et al , 2003; Carter et al , 2003; Hussein and Kiwia, 2009; Oba and Fodio, 2013). On the other hand, other studies found no significant relationship or the relationship found was negative (Shrader et al , 1997; Rose, 2007; Rand, 2013), because other variables beyond gender diversity may have interfered with the performance, such as qualifications and experience (Almeida-Santos et al , 2013).…”
Section: Theoretical Foundationmentioning
confidence: 98%
See 2 more Smart Citations
“…Dessa forma, empresas pertencentes ao ISE possuem maior legitimidade junto aos investidores, em relação a eficiência econômica, ambiental, social e de governança corporativa. Logo, os resultados obtidos sustentam essas afirmativas e corroboram com pesquisas anteriores, como a deAlmeida-Santos et al (2013) eCristófalo et al (2016).…”
unclassified